Perencanaan Pembangunan Berdasarkan Transformasi Pembangunan Ekonomi Sektoral: Studi Kasus Kabupaten Karanganyar Provinsi Jawa Tengah - Hizkia Setya Simangunsong; Suryanto Suryanto; Evi Gravitiani (Universitas Batanghari Jambi, 2026)
This study analyzes the transformation of sectoral economic development in Karanganyar Regency, Central Java Province, with a focus on identifying leading sectors and formulating strategies for sustainable and inclusive development planning. The research employs a combination of descriptive and quantitative analysis using the Klassen Typology approach to classify sectors based on their contribution to regional GDP and growth rate. The results show that the Advanced and Rapidly Growing Sectors include Manufacturing and Accommodation and Food Service Activities; the Rapidly Growing Sectors include Construction; Wholesale and Retail Trade; Repair of Motor Vehicles and Motorcycles; Business Services; and Other Services. The Advanced but Depressed Sectors comprise Electricity and Gas Supply; Water Supply, Waste Management, and Recycling; Financial and Insurance Activities; and Real Estate. Meanwhile, the Relatively Underdeveloped Sectors include Agriculture, Forestry, and Fisheries; Mining and Quarrying; Transportation and Warehousing; Information and Communication; Public Administration, Defense, and Mandatory Social Security; Education; and Health and Social Work Activities. The policy implications include: (1) optimizing industrial and tourism sectors as key drivers of economic growth, (2) revitalizing agriculture through technology adoption, and (3) strengthening modern service sectors such as information and communication as well as finance. This study provides specific recommendations for aligning the Regional Medium-Term Development Plan (RPJMD) to promote inclusive and sustainable economic transformation in Karanganyar Regency